2014
DOI: 10.2310/7750.2013.13130
|View full text |Cite
|
Sign up to set email alerts
|

Angiofibroma of the Vulva

Abstract: Background: Cellular angiofibroma is a benign and rare tumor. It usually arises in middle-aged women and involves the vulva.Complete local excision of the tumor is the best cure, and, usually, there is no recurrence after surgery.Case Report: We describe a 20-year-old woman with a painless, growing vulvar mass who presented about 3 years ago. Her past medical history was negative for oral contraceptives, tobacco, and alcohol, and there were no similar lesions in her family history. A physical examination revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Outside the vulvo-vaginal region, 5 pelvic localizations are reported, including 4 perineum and an urethral site. Six extra-pelvic CA are reported, such as a left hip, lateral knee, chest wall, left axilla and breasts [ 10 ], left hypocondrium [ 3 , 5 ] and more recently, we have reported the first case of retroperitoneal CA arising in right paravesical space of a post-menopausal woman [ 11 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside the vulvo-vaginal region, 5 pelvic localizations are reported, including 4 perineum and an urethral site. Six extra-pelvic CA are reported, such as a left hip, lateral knee, chest wall, left axilla and breasts [ 10 ], left hypocondrium [ 3 , 5 ] and more recently, we have reported the first case of retroperitoneal CA arising in right paravesical space of a post-menopausal woman [ 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…Six extra-pelvic CA are reported in literature. Exceptionally, a young woman presented both vulvar and extra-pelvic CA, particularly two vulvar CA on the right and the left labia majora and three extravulvar CA on the left axilla and both breasts were reported [ 10 ].…”
Section: Reviewmentioning
confidence: 99%
“…Vulvar angiofibroma usually occurs as a small lesion (usually less than 4 cm) with well-circumscribed margins [4]. In our case, the tumor was larger and did not have a well-defined capsule, also, at the distal pole of the tumor, a clear plane of cleavage with the vaginal wall was not found, making the resection difficult at this point and having to remove part of the vaginal mucosa.…”
Section: Discussionmentioning
confidence: 56%
“…It is found most frequently in middle-aged women around the fifth decade [2], however Amadhnia et al reported a case of a 20-year-old woman [4]. It occurs equally in both sexes and most often arises in the inguinoscrotal or vulvovaginal regions, although cases occurring in extragenital locations such as perineum, chest wall and retroperitoneum have also been described [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…[8] The youngest report of vulvar CA was from a 20-year-old patient with additional lesions on the axilla and breast. [9] In addition, the most recent peculiar site is CA of the orbit as described by Hötte et al [10]…”
Section: Discussionmentioning
confidence: 99%